Heat conduction material

JP2025023579APending Publication Date: 2025-02-17KITAGAWA INDS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023127848
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-17

Smart Images

  • Figure 2025023579000001_ABST
    Figure 2025023579000001_ABST
Patent Text Reader

Abstract

To provide a heat conduction material that is easier to manufacture than conventional products and has excellent thermal conductivity and insulation properties.SOLUTION: A heat conduction material is a laminate of alternating layers of thermally conductive and insulating layers. The thermally conductive layers are 0.5 to 2 mm thick layers of thermally conductive material with thermal conductivity 3 W / m K to 5 W / m K and volume resistivity 1×1010 Ω cm-1×1012 Ω cm. The insulating layers are 1 μm-100 μm thick layers of insulating material with thermal conductivity 0.1 W / m K to 0.6 W / m K and volume resistivity 1×1016 Ω cm-1×1019 Ω cm. The laminate is 1 mm to 4 mm thick and has a withstand voltage of 2.5 kV / mm to 10 kV / mm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to thermally conductive materials. [Background technology]

[0002] A thermally conductive insulating sheet has been proposed (see, for example, Patent Document 1). In the thermally conductive insulating sheet described in Patent Document 1, when the sheet is 80 μm thick or more, the voids existing within an area of ​​20 μm from both surfaces of the sheet have an area ratio of 8% or less. When the sheet is 25 μm thick or more but less than 80 μm, the voids existing within an area of ​​10 μm from both surfaces of the sheet have an area ratio of 8% or less. In other words, the technology described in Patent Document 1 improves the insulating properties of the sheet by controlling the void ratio (air bubble ratio) within a specified area inside the sheet. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2021-122008 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, it is not necessarily easy to appropriately control the void ratio inside the sheet, and there are drawbacks such as the number of steps required to produce the sheet being greater than in general coater molding. In one aspect of the present disclosure, it is desirable to provide a thermally conductive material that is easier to manufacture than conventional products and has excellent thermal conductivity and electrical insulation properties. [Means for solving the problem]

[0005] One aspect of the present disclosure is a thermally conductive material that is formed of a laminate in which a plurality of thermally conductive layers and a plurality of insulating layers are alternately laminated. The thermally conductive layers have a thermal conductivity of 3 W / m K-5 W / m K and a volume resistivity of 1×10 10Ω cm-1×10 12 The insulating layer is a 0.5-2 mm thick layer of thermally conductive material with a thermal conductivity of 0.1 W / m K-0.6 W / m K and a volume resistivity of 1×10 16 Ω cm-1×10 19 The laminate is made of insulating material with a thickness of 1 μm-100 μm and a dielectric strength of Ω·cm. The laminate is made to a thickness of 1 mm-4 mm and has a dielectric strength of 2.5 kV / mm-10 kV / mm.

[0006] According to the thermal conductive material thus constructed, since the thermal conductive material is composed of the above-mentioned laminate, it becomes a thermal conductive material with excellent thermal conductivity and insulation properties. Moreover, since the thermal conductive material is composed of the above-mentioned laminate, unlike the conventional technology, a process for appropriately controlling the porosity inside the sheet is not required, so that the thermal conductive material having the desired performance can be easily manufactured.

[0007] In addition, in one aspect of the present disclosure, the following configuration may be adopted. In one embodiment of the present disclosure, the thermally conductive material may contain 20 parts by weight to 25 parts by weight of an acrylic resin, 250 parts by weight to 300 parts by weight of alumina particles having an average particle size of 2 μm to 100 μm, 4 parts by weight to 13 parts by weight of magnesium hydroxide particles having an average particle size of 0.5 μm to 1.5 μm, 50 parts by weight to 60 parts by weight of silicon carbide particles having an average particle size of 50 μm to 100 μm, and 1 part by weight to 3 parts by weight of a plasticizer.

[0008] In one embodiment of the present disclosure, the alumina particles may include small alumina particles having an average particle size of 2 μm-10 μm and large alumina particles having an average particle size of 50 μm-100 μm in a volume ratio of 2:3-2:5.

[0009] In one embodiment of the present disclosure, the insulating material may be at least one of a polyolefin resin, a polyester resin, and a fluororesin. In one embodiment of the present disclosure, the insulating layer may be composed of a polyester resin film having a hydrophilized surface with a water contact angle of 13°-26°. [Brief description of the drawings]

[0010] [Figure 1] Fig. 1A is a schematic diagram showing a thermally conductive material of Example 1-1, Fig. 1B is a schematic diagram showing a thermally conductive material of Comparative Example 1-1, and Fig. 1C is a schematic diagram showing a thermally conductive material of Comparative Example 1-2. [Diagram 2] Fig. 2A is a schematic diagram showing a thermally conductive material of Example 2-1, Fig. 2B is a schematic diagram showing a thermally conductive material of Comparative Example 2-1, and Fig. 2C is a schematic diagram showing a thermally conductive material of Comparative Example 2-2. [Diagram 3] Fig. 3A is a schematic diagram showing a thermally conductive material of Example 3-1. Fig. 3B is a schematic diagram showing a thermally conductive material of Comparative Example 3-1. Fig. 3C is a schematic diagram showing a thermally conductive material of Comparative Example 3-2. Fig. 3D is a schematic diagram showing a thermally conductive material of Comparative Example 3-3. Fig. 3E is a schematic diagram showing a thermally conductive material of Comparative Example 3-4. [Figure 4] Fig. 4A is a schematic diagram showing the thermally conductive materials of Examples 4-1, 4-2, 4-3, and 4-4, and Fig. 4B is a graph showing the relationship between the water contact angle and the withstand voltage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Next, the above-mentioned thermally conductive material will be described with reference to exemplary embodiments. (1) First embodiment First, the first embodiment will be described.

[0012] [Thermal Conductive Material Composition] 1A shows a thermally conductive material 1 of the first embodiment. The thermally conductive material 1 has a structure in which a thermally conductive layer 11A, an insulating layer 12A, a thermally conductive layer 11B, and an insulating layer 12B are laminated in this order. That is, in the case of the first embodiment, the thermally conductive material 1 is composed of a laminate in which two thermally conductive layers 11A and 11B and two insulating layers 12A and 12B are alternately laminated. In addition, in the case of the first embodiment, a liner 13 is further laminated at a position in contact with one surface of the thermally conductive layer 11A.

[0013] The thermally conductive layers 11A and 11B have adhesiveness, and the insulating layers 12A and 12B and the liner 13 are adhered to the thermally conductive layers 11A and 11B by utilizing this adhesiveness. When the thermally conductive material 1 is used, the liner 13 is peeled off from the thermally conductive material 1. This allows the thermally conductive material 1 to be attached to the attachment target location by utilizing the adhesiveness of the thermally conductive layer 11A. When arranging the thermally conductive material between a member on the upstream side in the thermal conduction direction and a member on the downstream side in the thermal conduction direction, the thermally conductive material 1 is attached to one of the members as the attachment target location, and the other member is brought into contact with the thermally conductive material 1.

[0014] In the first embodiment, the thermally conductive layers 11A and 11B have a thermal conductivity of 5.0 W / m K and a volume resistivity of 1.0×10 11 The insulating layers 12A and 12B are made of a thermally conductive material with a thermal conductivity of 0.25 W / m K and a volume resistivity of 1.0×10 18 In the first embodiment, the insulating layers 12A and 12B are made of a polyester resin film (more specifically, a PET film).

[0015] In the first embodiment, the thermally conductive layers 11A, 11B are designed to have a thickness of 1 mm. The insulating layers 12A, 12B are designed to have a thickness of 5 μm. However, there is a slight error in the thicknesses of the thermally conductive layers 11A, 11B and the insulating layers 12A, 12B. Therefore, the actual thickness of the thermally conductive material 1 is about 2 mm.

[0016] [Composition of thermally conductive materials] Next, the thermal conductive material constituting the thermal conductive layers 11A and 11B will be described. The thermal conductive material exemplified in this embodiment contains 20-25 parts by mass of acrylic resin, 250-300 parts by mass of alumina particles with an average particle size of 2-100 μm, 4-13 parts by mass of magnesium hydroxide particles with an average particle size of 0.5-1.5 μm, 50-60 parts by mass of silicon carbide particles with an average particle size of 50-100 μm, and 1-3 parts by mass of plasticizer.

[0017] In the present embodiment, the acrylic resin is obtained by polymerizing or copolymerizing a (meth)acrylic acid ester. Examples of (meth)acrylic acid esters include ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-hexyl (meth)acrylate, n-amyl (meth)acrylate, i-amyl (meth)acrylate, octyl (meth)acrylate, i-octyl (meth)acrylate, i-myristyl (meth)acrylate, lauryl (meth)acrylate, nonyl (meth)acrylate, i-nonyl (meth)acrylate, i-decyl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, i-stearyl (meth)acrylate, etc. These may be used alone or in combination of two or more types when (co)polymerizing.

[0018] When polymerizing or copolymerizing the (meth)acrylic acid ester, for example, a polyfunctional monomer and a polymerization initiator are added to the above-mentioned acrylic resin. In this case, the polyfunctional monomer may be, for example, one having two or more (meth)acryloyl groups in the molecule.

[0019] The alumina particles are mixed in a ratio of 250-300 parts by mass to 20-25 parts by mass of the acrylic resin. The mixing ratio with respect to the total volume of the thermally conductive material is 70-75% by volume. The alumina particles are preferably roughly spherical particles. The alumina particles preferably have a soluble sodium content of 100 ppm or more, more preferably 120 ppm or more. The soluble sodium content is the amount of sodium ions (Na ions) that dissolve in water when the alumina particles are brought into contact with water. + ) amount.

[0020] The alumina particles may be a mixture of small alumina particles having an average particle size of 2 μm-10 μm and large alumina particles having an average particle size of 50 μm-100 μm in a volume ratio of 2:3-2:5. These alumina particles are preferably spherical particles. The particle size of the alumina particles is indicated by the average particle size D50 obtained by, for example, a laser diffraction method. When the alumina particles having the above-mentioned particle size are mixed in the above-mentioned mixing ratio, the packing density of the alumina particles in the thermally conductive material can be increased.

[0021] The magnesium hydroxide particles preferably have an average particle size of 0.5 μm to 1.5 μm. The particle size of the magnesium hydroxide particles is indicated by, for example, the average particle size D50 determined by a laser diffraction method or the like. The magnesium hydroxide particles are preferably particles coated with a higher fatty acid. Examples of the higher fatty acid include palmitic acid, stearic acid, oleic acid, and linoleic acid.

[0022] The magnesium hydroxide particles are mixed in a ratio of 4 parts by mass to 13 parts by mass to 20 parts by mass to 25 parts by mass of the acrylic resin, and the mixing ratio to the total volume of the thermal conductive material is 2.7% by volume to 5.3% by volume.

[0023] The silicon carbide particles are mixed in a ratio of 50 to 60 parts by mass to 20 to 25 parts by mass of the acrylic resin. The plasticizer may be a general-purpose one, and is preferably, for example, a phthalic acid-based, adipic acid-based, phosphoric acid-based, trimellitic acid-based, polyester-based, etc. These plasticizers may be used alone or in combination of two or more. The incorporation of a plasticizer imparts flexibility to the thermally conductive material.

[0024] The plasticizer is preferably mixed in a ratio of 1.2 to 2.8 parts by mass per 20 to 25 parts by mass of the acrylic resin. By making the mixing ratio of the plasticizer 1.2 parts by mass or more, the effect of adding the plasticizer is manifested, and the hardness of the thermal conductive material is reduced. In addition, by making the mixing ratio of the plasticizer 2.8 parts by mass or less, the plasticizer can be prevented from seeping out (bleeding) from the surface of the thermal conductive material.

[0025] In addition to the main components described above, the thermally conductive material may contain other components within the scope of not impairing the function of the thermally conductive material. Examples of the other components include antioxidants, flame retardants, lubricants, ultraviolet absorbers, stabilizers, dispersants, colorants, antistatic agents, and preservatives.

[0026] [Performance test] The thermal resistance and withstand voltage of the thermal conductive material 1 (hereinafter referred to as Example 1-1) were measured. The thermal resistance was measured using a measuring device conforming to the ASTM D5470 standard. The withstand voltage was measured using a measuring device conforming to the JIS C2110-1 standard. For comparison, a thermal conductive material C1A (hereinafter referred to as Comparative Example 1-1) and a thermal conductive material C1B (hereinafter referred to as Comparative Example 1-2) were prepared as shown in FIG. 1B and FIG. 1C. The thermal conductive material C1A has a structure in which a thermal conductive layer 11A, a thermal conductive layer 11B, an insulating layer 12A, and an insulating layer 12B are laminated in the stated order. That is, the thermal conductive material C1A is different from the thermal conductive material 1 in the order of lamination of the layers.

[0027] The thermal conductive material C1B has a structure in which a thermal conductive layer 11A, a thermal conductive layer 11B, an insulating layer 12A, an insulating layer 12B, and an insulating layer 12C are laminated in the stated order. That is, the thermal conductive material C1B has a structure in which an insulating layer 12C is further added to a laminate equivalent to the thermal conductive material C1A. The thermal resistance and withstand voltage of these thermal conductive materials C1A and C1B were measured. The results are shown in Table 1.

[0028] [Table 1]

[0029] From the measurement results shown in Table 1, it can be seen that Example 1-1 and Comparative Example 1-1 have smaller thermal resistance values ​​than Comparative Example 1-2. Therefore, it was suggested that increasing the number of insulating layers leads to a decrease in thermal resistance characteristics. In addition, it can be seen that Example 1-1 and Comparative Example 1-2 have larger withstand voltage values ​​than Comparative Example 1-1. Therefore, it was suggested that it is possible to obtain withstand voltage characteristics equivalent to those obtained when the number of insulating layers is increased, even without increasing the number of insulating layers, by devising the stacking order of the thermal conductive layers and the insulating layers. In addition, since it is not necessary to increase the number of insulating layers to obtain the desired withstand voltage characteristics, it is possible to reduce the thermal resistance accordingly.

[0030] As a standard for the rated impulse withstand voltage, a withstand voltage of 2.5 kV / mm or more is required for information processing equipment, portable tools, and household appliances. In the case of the above Example 1-1, since the withstand voltage value corresponds to 2.5 kV / mm or more, it can be said that the desired withstand voltage characteristics are provided. Note that, although a higher withstand voltage is more desirable, when assuming use in information processing equipment, portable tools, and household appliances, a practical withstand voltage of 10 kV / mm or less is sufficient. In other words, the withstand voltage of the thermal conductive material 1 may be 2.5 kV / mm-10 kV / mm.

[0031] Therefore, the thermal conductive material 1 having the above-mentioned configuration can have both excellent thermal resistance characteristics and excellent voltage resistance characteristics. Also, unlike conventional products in which the voltage resistance characteristics are improved by controlling the porosity within the sheet, the thermal conductive material 1 having the above-mentioned configuration does not require a process for appropriately controlling the porosity, so that the desired thermal conductive material can be easily manufactured.

[0032] (2) Second embodiment Next, a second embodiment will be described. However, since the second and subsequent embodiments have many configurations similar to those exemplified in the first embodiment, the following description will focus on the differences from the first embodiment, and a detailed description of the configurations similar to those of the first embodiment will be omitted.

[0033] [Thermal Conductive Material Composition] 2A shows the thermally conductive material 2 of the second embodiment. The thermally conductive material 2 has a structure in which a thermally conductive layer 21A, an insulating layer 22A, a thermally conductive layer 21B, an insulating layer 22B, a thermally conductive layer 21C, and an insulating layer 22C are laminated in this order. That is, in the case of the second embodiment, the thermally conductive material 2 is composed of a laminate in which three thermally conductive layers 21A, 21B, and 21C and three insulating layers 22A, 22B, and 22C are alternately laminated. As in the first embodiment, a liner 23 is laminated at a position in contact with one surface of the thermally conductive layer 21A.

[0034] The thermally conductive material constituting the thermally conductive layers 21A, 21B, and 21C is the same as that in the first embodiment. The insulating material constituting the insulating layers 22A, 22B, and 22C is the same as that in the first embodiment. In the second embodiment, the thermally conductive layers 21A, 21B, and 21C are designed to have a thickness of 0.5 mm. The insulating layers 22A, 22B, and 22C are designed to have a thickness of 5 μm. However, there is a slight error in the thicknesses of the thermally conductive layers 21A, 21B, and 21C and the insulating layers 22A, 22B, and 22C. Therefore, the actual thickness of the thermally conductive material 2 is about 1.5 mm.

[0035] [Performance test] The thermal resistance and withstand voltage of the thermally conductive material 2 (hereinafter referred to as Example 2-1) were measured. The measurement method was the same as that of the first embodiment. For comparison, a thermally conductive material C2A (hereinafter referred to as Comparative Example 2-1) and a thermally conductive material C2B (hereinafter referred to as Comparative Example 2-2) were prepared as shown in Figs. 2B and 2C. The thermally conductive material C2A has a structure in which a thermally conductive layer 21A, a thermally conductive layer 21B, a thermally conductive layer 21C, an insulating layer 22A, an insulating layer 22B, and an insulating layer 22C are laminated in the stated order. That is, the thermally conductive material C2A is different from the thermally conductive material 2 in the order in which the layers are laminated.

[0036] The thermal conductive material C2B has a structure in which the thermal conductive layer 11A, the thermal conductive layer 11B, the insulating layer 12A, the insulating layer 12B, the insulating layer 12C, and the insulating layer 12D are laminated in the stated order. In other words, the thermal conductive material C2B has a structure in which the insulating layer 12D is further added to a laminate equivalent to the thermal conductive material C2A. The thermal resistance and the withstand voltage of these thermal conductive materials C2A and C2B were measured. The results are shown in Table 2.

[0037] [Table 2]

[0038] From the measurement results shown in Table 2, it can be seen that Example 2-1 and Comparative Example 2-1 have smaller thermal resistance values ​​than Comparative Example 2-2. Therefore, it was suggested that increasing the number of insulating layers leads to a decrease in thermal resistance characteristics. It can also be seen that Example 2-1 has a larger withstand voltage value than Comparative Example 2-1 and Comparative Example 2-2. Comparative Example 2-2 has more insulating layers than Example 2-1 because it has insulating layer 12D, but its withstand voltage value is smaller than that of Example 2-1. Therefore, it was suggested that even without increasing the number of insulating layers, by devising the stacking order of the thermal conduction layers and the insulating layers, it is possible to obtain withstand voltage characteristics that are greater than those obtained when the number of insulating layers is increased. In addition, since it is not necessary to increase the number of insulating layers to obtain the desired withstand voltage characteristics, it is possible to reduce the thermal resistance accordingly. In the case of the above-mentioned Example 2-1, since the withstand voltage value corresponds to 2.5 kV / mm-10 kV / mm, it can be said that it has the desired withstand voltage characteristics.

[0039] Therefore, the thermal conductive material 2 having the above-mentioned configuration can have both excellent thermal resistance characteristics and excellent voltage resistance characteristics. Moreover, unlike conventional products in which the voltage resistance characteristics are improved by controlling the porosity within the sheet, the thermal conductive material 2 having the above-mentioned configuration does not require a process for appropriately controlling the porosity, so that the desired thermal conductive material can be easily manufactured.

[0040] (3) Third embodiment [Thermal Conductive Material Composition] FIG. 3A shows the thermal conductive material 3 of the third embodiment. The thermal conductive material 3 is configured in the same manner as the thermal conductive material 1 of the first embodiment. Specifically, the thermal conductive material 3 has a structure in which a thermal conductive layer 31A, an insulating layer 32A, a thermal conductive layer 31B, and an insulating layer 32B are laminated in this order. The liner 33 is laminated at a position in contact with one surface of the thermal conductive layer 31A, the thermal conductive material constituting the thermal conductive layers 31A and 31B, and the insulating material constituting the insulating layers 32A and 32B are all the same as those of the first embodiment. In the third embodiment, the thermal conductive layers 31A and 31B are designed to have a thickness of 0.5 mm. The insulating layers 32A and 32B are designed to have a thickness of 5 μm. However, there is a slight error in the thicknesses of the thermal conductive layers 31A and 31B and the insulating layers 32A and 32B. Therefore, the actual thickness of the thermally conductive material 3 is about 1.5 mm, but when comparing the thermally conductive material 1 of the first embodiment and the thermally conductive material 3 of the third embodiment, the measured thicknesses are different.

[0041] [Performance test] The withstand voltage of the thermally conductive material 3 (hereinafter referred to as Example 3-1) was measured. The measurement method was the same as that of the first embodiment. For comparison, thermally conductive material C3A (hereinafter referred to as Comparative Example 3-1), thermally conductive material C3B (hereinafter referred to as Comparative Example 3-2), thermally conductive material C3C (hereinafter referred to as Comparative Example 3-3), and thermally conductive material C3D (hereinafter referred to as Comparative Example 3-4) were prepared as shown in Figures 3B, 3C, 3D, and 3E. The thermally conductive material C3A has a structure in which a thermally conductive layer 31A, a thermally conductive layer 31B, an insulating layer 32A, and an insulating layer 32B are laminated in the stated order. That is, the thermally conductive material C3A is different from the thermally conductive material 3 in the order of lamination of the layers.

[0042] The thermal conductive material C3B has a structure in which the thermal conductive layer 31A, the insulating layer 32A, and the thermal conductive layer 31B are laminated in the stated order. That is, the thermal conductive material C3B has a structure in which the insulating layer 32B is removed from the thermal conductive material 3. The thermal conductive material C3C has a structure in which the thermal conductive layer 31A, the thermal conductive layer 31B, and the insulating layer 32B are laminated in the stated order. That is, the thermal conductive material C3C has a structure in which the insulating layer 32A is removed from the thermal conductive material 3. The thermal conductive material C3D has a structure in which the thermal conductive layer 31A and the thermal conductive layer 31B are laminated in the stated order. That is, the thermal conductive material C3D has a structure in which the insulating layers 32A and 32B are removed from the thermal conductive material 3. The withstand voltages of these thermal conductive materials C2A, C2B, C2C, and C2D were measured. The results are shown in Table 3.

[0043] [Table 3]

[0044] From the measurement results shown in Table 3, it can be seen that the withstand voltage value decreases in the order of Example 3-1, Comparative Example 3-1, Comparative Example 3-2, Comparative Example 3-3, and Comparative Example 3-4. Both Example 3-1 and Comparative Example 3-1 have two insulating layers 32A and 32B, but the withstand voltage characteristic of Example 3-1 is superior to that of Comparative Example 3-1. Therefore, it was suggested that excellent withstand voltage characteristics can be obtained by devising the stacking order of the thermal conduction layer and the insulating layer. In addition, since it is not necessary to increase the number of insulating layers to obtain the desired withstand voltage characteristic, it is possible to reduce the thermal resistance accordingly. In the case of the above-mentioned Example 3-1, since the withstand voltage value corresponds to 2.5 kV / mm-10 kV / mm, it can be said that it has the desired withstand voltage characteristic.

[0045] (4) Fourth embodiment [Thermal Conductive Material Composition] 4A shows a thermally conductive material 4 of the fourth embodiment. The thermally conductive material 4 is configured in the same manner as the thermally conductive material 1 of the first embodiment. Specifically, the thermally conductive material 4 has a structure in which a thermally conductive layer 41A, an insulating layer 42A, a thermally conductive layer 41B, and an insulating layer 42B are laminated in this order. The liner 43 is laminated at a position in contact with one surface of the thermally conductive layer 41A, the thermally conductive material constituting the thermally conductive layers 41A and 41B, and the insulating material constituting the insulating layers 42A and 42B are all the same as those of the first embodiment.

[0046] However, in the fourth embodiment, the insulating layers 42A and 42B are made of polyester resin films having hydrophilic surfaces. More specifically, in the fourth embodiment, one side of the polyester resin films constituting the insulating layers 42A and 42B is subjected to a corona discharge treatment, and the one side is made into a hydrophilic surface.

[0047] In the fourth embodiment, the thermally conductive layers 41A, 41B are designed to have a thickness of 0.5 mm. The insulating layers 42A, 42B are designed to have a thickness of 5 μm. However, there is a slight error in the thicknesses of the thermally conductive layers 41A, 41B and the insulating layers 42A, 42B. Therefore, the actual thickness of the thermally conductive material 4 is about 1.5 mm, but when comparing the thermally conductive material 1 of the first embodiment and the thermally conductive material 4 of the fourth embodiment, the measured thicknesses are different.

[0048] [Performance test] The treatment time of the corona discharge treatment was changed in four ways to prepare four types of polyester resin films with different hydrophilicity, and the four types of polyester resin films were used to prepare four types of thermally conductive materials 4. A commercially available corona discharge surface modification device (product name: Corona Fit CFA-500, manufactured by Shinko Electric Instrumentation Co., Ltd., output voltage 9 kV) was used to carry out the corona discharge treatment. Hereinafter, the four types of thermally conductive materials 4 are referred to as Example 4-1, Example 4-2, Example 4-3, and Example 4-4, respectively.

[0049] The hydrophilicity of the surface of the polyester resin film can be evaluated by the water contact angle. The water contact angles of Example 4-1, Example 4-2, Example 4-3, and Example 4-4 are 13 degrees, 26 degrees, 35 degrees, and 92 degrees, respectively, and it can be said that the smaller the water contact angle, the higher the wettability (hydrophilicity) of the surface. The voltage resistance of these Examples 4-1, 4-2, 4-3, and 4-4 was measured. The results are shown in Table 4 and FIG. 4B.

[0050] [Table 4]

[0051] From the measurement results shown in Table 4, it can be said that the withstand voltage values ​​in all of Examples 4-1, 4-2, 4-3, and 4-4 are 2.5 kV / mm-10 kV / mm, and therefore the desired withstand voltage characteristics are provided. In particular, in the case of Examples 4-1 and 4-2, the withstand voltage characteristics are significantly improved compared to Examples 4-3 and 4-4. Therefore, from the viewpoint of improving the withstand voltage characteristics, it can be said that it is effective for the insulating layer to be made of a polyester resin film having a hydrophilized surface with a water contact angle of 13°-26°.

[0052] The reason why the withstand voltage improves when the surface of the polyester resin film constituting the insulating layer is hydrophilized has not been clearly elucidated at present. However, when the surface of the polyester resin film is hydrophilized by corona discharge treatment, carbonyl groups and hydroxyl groups are generated on the surface of the film. This may improve the adhesion between the insulating layer and the thermally conductive layer, making it difficult for fine air particles to enter the interface between the insulating layer and the thermally conductive layer. It is speculated that when there is less air entering the interface between the insulating layer and the thermally conductive layer, it becomes difficult for the current to choose the shortest path, resulting in improved insulation.

[0053] (5) Fifth embodiment In the thermally conductive material 1 of the first embodiment, the insulating layers 12A and 12B are made of a polyester resin film. Instead of this, the insulating layers 12A and 12B are made of a polyolefin resin film (more specifically, a polypropylene film). The polyolefin resin film used in the fifth embodiment has a volume resistivity of 1.0×10 16 The thermal conductive material of the fifth embodiment has a withstand voltage value of 2.5 kV / mm to 10 kV / mm, which is the desired withstand voltage characteristic.

[0054] As the polyolefin resin film, a polyethylene film may be used. (6) Sixth embodiment In the thermal conductive material 1 of the first embodiment, the insulating layers 12A and 12B are made of a polyester resin film. Instead of this, the insulating layers 12A and 12B are made of a fluororesin film (more specifically, a PTFE film). The fluororesin film used in the sixth embodiment has a volume resistivity of 1.0×10 18 The thermal conductive material of the sixth embodiment has a withstand voltage value of 2.5 kV / mm to 10 kV / mm, and thus has the desired withstand voltage characteristics.

[0055] As the fluororesin film, a PFA film or an FEP film may be used. (7) Other embodiments Although the thermally conductive material has been described above by way of exemplary embodiments, the above-mentioned embodiments are merely exemplified as one aspect of the present disclosure. In other words, the present disclosure is not limited to the above-mentioned exemplary embodiments, and can be embodied in various forms without departing from the technical concept of the present disclosure.

[0056] For example, in the above embodiment, an example was shown in which the thickness of the insulating layer was 5 μm, but the thickness of the insulating layer may be adjusted within the range of about 1 μm to 100 μm. In addition, in the above embodiments, examples in which the thickness of the thermally conductive layer is 1 mm and 0.5 mm are shown, but the thickness of the thermally conductive layer may be adjusted within a range of about 0.5 mm to 2 mm.

[0057] The thickness of the laminate constituting the thermal conductor may be adjusted within the range of about 1 mm to 4 mm. In addition, multiple functions realized by one component exemplified in the above embodiments may be realized by multiple components. One function realized by one component exemplified in the above embodiments may be realized by multiple components. Multiple functions realized by multiple components exemplified in the above embodiments may be realized by one component. One function realized by multiple components exemplified in the above embodiments may be realized by one component. Part of the configuration exemplified in the above embodiments may be omitted. At least part of the configuration exemplified in one of the above embodiments may be added to or replaced with the configuration exemplified in the above embodiments other than that one embodiment.

[0058] (8) Technical idea disclosed in this specification [Item 1] The laminate is made up of a plurality of thermally conductive layers and a plurality of insulating layers stacked alternately, The thermally conductive layer has a thermal conductivity of 3 W / m K-5 W / m K and a volume resistivity of 1×10 10 Ω cm-1×10 12 A layer of material with a thermal conductivity of Ω·cm, 0.5-2 mm thick. The insulating layer has a thermal conductivity of 0.1 W / m K to 0.6 W / m K and a volume resistivity of 1×10 16 Ω cm-1×10 19 A layer of 1-100μm thick made of insulating material with an Ω·cm resistance. The laminate is configured to a thickness of 1 mm to 4 mm and has a withstand voltage of 2.5 kV / mm to 10 kV / mm. Thermally conductive material.

[0059] [Item 2] Item 1. The thermally conductive material according to item 1, The thermally conductive material contains 20-25 parts by mass of an acrylic resin, 250-300 parts by mass of alumina particles having an average particle size of 2 μm-100 μm, 4-13 parts by mass of magnesium hydroxide particles having an average particle size of 0.5 μm-1.5 μm, 50-60 parts by mass of silicon carbide particles having an average particle size of 50 μm-100 μm, and 1-3 parts by mass of a plasticizer. Thermally conductive material.

[0060] [Item 3] Item 2. The thermally conductive material according to item 2, The alumina particles include small alumina particles having an average particle size of 2 μm-10 μm and large alumina particles having an average particle size of 50 μm-100 μm in a volume ratio of 2:3-2:5. Thermally conductive material.

[0061] [Item 4] The thermal conductive material according to any one of items 1 to 3, The insulating material is at least one of a polyolefin resin, a polyester resin, and a fluororesin. Thermally conductive material.

[0062] [Item 5] Item 5. The thermally conductive material according to item 4, The insulating layer is composed of a polyester resin film having a hydrophilic surface with a water contact angle of 13°-26°. Thermally conductive material. [Explanation of symbols]

[0063] 1, 2, 3, 4...thermal conductive material, 11A, 11B, 21A, 21B, 21C, 31A, 31B, 41A, 41B...thermal conductive layer, 12A, 12B, 12C, 12D, 22A, 22B, 22C, 32A, 32B, 42A, 42B...insulating layer, 13, 23, 33, 43...liner.

Claims

1. The laminate is made up of a plurality of thermally conductive layers and a plurality of insulating layers stacked alternately, The thermally conductive layer has a thermal conductivity of 3 W / m·K to 5 W / m·K and a volume resistivity of 1×10 10 Ω・cmΩ・cm-1×10 12 A layer of 0.5 mm-2 mm thickness made of a material with a thermal conductivity of Ω cm; The insulating layer has a thermal conductivity of 0.1 W / m·K to 0.6 W / m·K and a volume resistivity of 1×10 16 Ω cm-1×10 19 A layer of 1 μm-100 μm thick made of an insulating material with an Ω cm resistance. The laminate is configured to a thickness of 1 mm to 4 mm and has a withstand voltage of 2.5 kV / mm to 10 kV / mm. Thermally conductive material.

2. 2. The thermally conductive material according to claim 1 , The thermally conductive material contains 20-25 parts by mass of an acrylic resin, 250-300 parts by mass of alumina particles having an average particle size of 2-100 μm, 4-13 parts by mass of magnesium hydroxide particles having an average particle size of 0.5-1.5 μm, 50-60 parts by mass of silicon carbide particles having an average particle size of 50-100 μm, and 1-3 parts by mass of a plasticizer. Thermally conductive material.

3. The thermal conductive material according to claim 2, The alumina particles contain small alumina particles having an average particle size of 2 μm to 10 μm and large alumina particles having an average particle size of 50 μm to 100 μm in a volume ratio of 2:3 to 2:

5. Thermally conductive material.

4. The thermal conductive material according to any one of claims 1 to 3, The insulating material is at least one of a polyolefin resin, a polyester resin, and a fluororesin. Thermally conductive material.

5. The thermal conductive material according to claim 4, The insulating layer is composed of a polyester resin film having a hydrophilic surface with a water contact angle of 13° to 26°. Thermally conductive material.

Citation Information

Patent Citations

  • Thermally conductive insulating sheet and composite member

    JP2021122008A